Dynamic Resilient Network Games With Applications to Multiagent Consensus - Nugraha, Yurid; Cetinkaya, Ahmet; Hayakawa, Tomohisa; Ishii, Hideaki; Zhu, Quanyan (IEEE transactions on control of network systems, 2021)
A cyber security problem in a networked system formulated as a resilient graph problem based on a game-theoretic approach is considered. The connectivity of the underlying graph of the network system is reduced by an attacker who removes some of the edges, whereas the defender attempts to recover them. Both players are subject to energy constraints so that their actions are restricted and cannot be performed continuously. For this two-stage game, we characterize the optimal strategies for the attacker and the defender in terms of edge connectivity and the number of connected components of the graph. The resilient graph game is then applied to a multiagent consensus problem, where the game is played repeatedly over time. In this article, we study how the attacks and the recovery on the edges affect the consensus process. Finally, we also provide numerical simulation to illustrate the results.